Weak intermolecular CH···N hydrogen bonding: determination of 13CH–15N hydrogen-bond mediated J couplings by solid-state NMR spectroscopy and first-principles calculations - Webber, AL; Yates, JR; Zilka, M; Sturniolo, S; Uldry, A-C; Corlett, EK; Pickard, CJ; Pérez-Torralba, M; Angeles Garcia, M; Santa Maria, D; Claramunt, RM; Brown, SP (American Chemical Society, 2019)
Weak hydrogen bonds are increasingly hypothesized to play key roles in a wide range of chemistry from catalysis to gelation to polymer structure. Here, 15N/13C spin-echo magic-angle spinning (MAS) solid-state nuclear magnetic resonance (NMR) experiments are applied to “view” intermolecular CH···N hydrogen bonding in two selectively labeled organic compounds, 4-[15N] cyano-4′-[13C2] ethynylbiphenyl (1) and [15N3,13C6]-2,4,6-triethynyl-1,3,5-triazine (2). The synthesis of 2-15N3,13C6 is reported here for the first time via a multistep procedure, where the key element is the reaction of [15N3]-2,4,6-trichloro-1,3,5-triazine (5) with [13C2]-[(trimethylsilyl)ethynyl]zinc chloride (8) to afford its immediate precursor [15N3,13C6]-2,4,6-tris[(trimethylsilyl)ethynyl]-1,3,5-triazine (9). Experimentally determined hydrogen-bond-mediated 2hJCN couplings (4.7 ± 0.4 Hz (1) and 4.1 ± 0.3 Hz (2)) are compared with density functional theory (DFT) gauge-including projector augmented wave (GIPAW) calculations, whereby species-independent coupling values 2hKCN (29.0 × 1019 kg m–2 s–2 A–2 (1) and 27.9 × 1019 kg m–2 s–2 A–2 (2)) quantitatively demonstrate the J couplings for these “weak” CH···N hydrogen bonds to be of a similar magnitude to those for conventionally observed NH···O hydrogen-bonding interactions in uracil (2hKNO: 28.1 and 36.8 × 1019 kg m–2 s–2 A–2). Moreover, the GIPAW calculations show a clear correlation between increasing 2hJCN (and 3hJCN) coupling and reducing C(H)···N and H···N hydrogen-bonding distances, with the Fermi contact term accounting for at least 98% of the isotropic 2hJCN coupling.